PENGARUH MODEL PEMBELAJARAN MID (MEANINGFUL INSTRUCTIONAL DESIGN)BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS CERPENDAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN DARING MATAPELAJARAN BAHASA INDONESIA KELAS V SD INPRES GALANGAN KAPAL 2 - Chaeriani; Andi Sukri Syamsuri; Tharman A. Arief (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to determine the significant effect of the Picture Media-Assisted MID (Meaningful Instructional Design) Learning Model on students' Short Story Writing Ability and Learning Motivation in Bahasa Indonesia Online at grade V of SD Inpres Galangan Kapal 2, Makassar. The design of this study was a non-equivalent control group design. The data analysis techniques were descriptive analysis and inferential analysistechniques through the independent sample T-test and the Manova test. The study results found that the average score of students' short story writing ability in the pre-test was 55.16, and the average score in the post-test after implementing the MID model was 82.20. Then, the Independent sample T-test results found that Tcount = 3.118 > Ttable = 2.021, and the sig. value was 0.003 < 0.05. Moreover, after using the MID model assisted by image media, the students' learning motivation results obtained a Tcount of 8.085 > Ttable of 2.021 with the sig. value of 0.000 < 0.05. Then, the results of the Manova test found that 0.000 <0.05, indicating that Ha was accepted and Ho was rejected. Thus, the picture media-assisted MID model significantly influenced the students' short story writing skills and motivation to learn Bahasa Indonesia online at grade V of SD Inpres Galangan Kapal 2, Makassar.